TANGGUNG JAWAB ORANG TUA TERHADAP ANAK DALAM PERSPEKTIF HUKUM ISLAM - Fajarwati Fajarwati (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2019)
Children are tests (trials). Allah Swt. said "verily your wealth and your children are only a trial (for you)." (Surat At-Taghabun: 15) And the word of God, "O you who believe, surely among your wives and your children there are enemies to you, so be careful of them and if you forgive and do not rebuke and forgive (they) then surely Allah Most Forgiving, Most Merciful. " (Surat AtTaghabun: 14). And Allah says: "treasures and children are the jewels of the world." (Surat al-Kahf: 46) Allah also said: "made beautiful in the (view) of man's love for what is desired, namely: women, children, wealth of many kinds of gold, silver, choice horses, livestock animals and rice fields. That is the pleasure of life on earth and in the sight of Allah is a good place to return (heaven). "(Surah Ali Imran: 14). Tests for children can arise from anywhere, including: God's gift of children can sometimes make a servant arrogant and not grateful for the blessings of God given to him. He is proud of his children, feels the highest of the people, arrogant and unjust. Then that will lead him to hell. Therefore, both parents must educate their children to obey Allah and make their growth in the pleasure of Allah. and parents should not be preoccupied by their children to disobey Allah and remember Allah. God has warned us not to be so busy with children that we forget to remember God. Allah says: "O you who rhyme, do not let your property and your children neglect you from remembering Allah. Whoever makes it that way, they are the losers. " (Surah Al Munafiqun: 9).